Non-maximality effects in gestural plural predication - Alexandropoulou, Stavroula; Erbach, Kurt; Breheny, Richard; Mayr, Clemens; Romoli, Jacopo; Sudo, Yasutada (Proceedings of the Amsterdam Colloquium, 2024)
The present paper investigates homogeneity and non-maximality of novel pro-speech gestures. Our experiment adopts and refines Tieu, Schlenker, and Chemla’s (2019) experimental design and also incorporate Romoli et al.’s (2024) idea of context manipulation. The results indicate not only that homogeneity inferences can arise from unfamiliar gestures but also that non-maximality triggered by gestural means is contextually modulated and is more robustly so in positive than in negative sentences. In light of Romoli et al.’s (2024) observation for plural definites, these findings point to the possibility that the mechanism responsible for homogeneity and non-maximality extends beyond conventionalized linguistic expressions to include unfamiliar gestures, aligning with the view that homogeneity and non-maximality emerge from productive semantic and pragmatic processes.